Perilaku Impor Susu di Indonesia - Hastuti Pratiwi; Abdul Hakim (Telaah Bisnis, 2016)
AbstractThis paper analyzes the behaviour of milk import in Indonesia during 1985-2010. Using an Error Correction Model (ECM), it finds that in the long run, factors influencing the milk import are percapita income, domestic milk real price, and imported milk price. In the short run, the import is influenced by population size of more than 5-year old residents, real domestic price milk, real price of imported milk, and exchange rates. Variables that do not influence milk imports, both in the short run and in the long run, are national milk production, milk exports, population size of less than 5-year old residents, and the gonvernment policy on the deletion of milk imports.